ChemInform Abstract: Chemistry of Intermolecular Frustrated Lewis Pairs in Motion: Emerging Perspectives and Prospects. Issue 16 (April 2015) - Pu, Maoping; Privalov, Timofei
Abstract Review: [72 refs.